APPLICATIONS OF MONTE CARLO SIMULATION TO STRUCTURAL ENGINEERING PROBLEMS (Nonconventional Technologies Review, 2024)
This paper investigates the application of Monte Carlo simulations in structural engineering to address various design optimization and uncertainty analysis. These applications include its uses in solving optimization problems and conducting uncertainty analysis. Three design problems are presented which are the design of a pressure vessel, the design of a rectangular welded beam, and the design of a compression spring. The performance of the Monte Carlo simulation along with other metaheuristic algorithms is compared numerically in the example problems. The comparison shows that the Monte Carlo simulation is a valid technique for structural design problems. The study concludes that despite its limitations, the simplicity and ease of implementation render Monte Carlo simulations an attractive option for structural design optimization scenarios where computational complexity may pose challenges.
Keywords: Structural Engineering; Optimization; Monté Carlo; Simulation; Metaheuristic